Investigating relationship dispositions as explanations for on-again/off-again relationships. (January 2020) - Dailey, René M.; Zhong, Lingzi; Pett, Rudy; Scott, Darby; Krawietz, Colton
The current study explored whether individuals with certain relationship dispositions were more likely to be involved in on-again/off-again (on-off) relationships. A sample of 211 currently dating participants in either on-off or non-cyclical relationships completed an online survey about relationship dispositions (e.g., attachment, implicit beliefs) and positive and negative aspects of relational quality (e.g., satisfaction, commitment, disillusionment). Participants in on-off relationships did not differ from those in non-cyclical relationships with regard to relationship dispositions. Relationship type, however, moderated certain associations between relationship dispositions and relationship qualities showing that the dispositions played a weaker role in relational quality for on-off partners (e.g., the association between growth belief and disillusionment was strong and negative for non-cyclical partners but nonsignificant for on-off partners). Although it was theoretically and practically important to investigate individual differences, interaction dynamics within dyads could be a more prominent factor in explaining on-off relationships.